2021
DOI: 10.5194/essd-2021-299
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estimating CO2 Emissions for 108,000 European Cities

Abstract: Abstract. City-level CO2 emissions inventories are foundational for supporting the EU’s decarbonization goals. Inventories are essential for priority setting and for estimating impacts from the decarbonization transition. Here we present a new CO2 emissions inventory for 116,572 municipal and local government units in Europe. The inventory spatially disaggregates the national reported emissions, using 9 spatialization methods to distribute the 167 line items detailed in the UN's Common Reporting Framework. The… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
(23 reference statements)
1
2
0
Order By: Relevance
“…The resulting r 2 = 0.91 indicates our model is strongly predictive overall of cities' self-reported emissions inventories. We further validated our predicted emissions with other studies that report emissions data for European cities, including Moran et al 15 , who estimate 2018 direct (Scope 1) emissions for more than 100,000 European cities and Nangini et al 16 , who combine self-reported inventories with other data for 343 global cities. We found fair correlation (r 2 = 0.57 with Moran et al 15 ; r 2 = 0.62 with Nangini et al 16 ) between our predicted data and these other studies (Supplementary Fig.…”
Section: City-level Predictors Of Climate Emissionssupporting
confidence: 68%
“…The resulting r 2 = 0.91 indicates our model is strongly predictive overall of cities' self-reported emissions inventories. We further validated our predicted emissions with other studies that report emissions data for European cities, including Moran et al 15 , who estimate 2018 direct (Scope 1) emissions for more than 100,000 European cities and Nangini et al 16 , who combine self-reported inventories with other data for 343 global cities. We found fair correlation (r 2 = 0.57 with Moran et al 15 ; r 2 = 0.62 with Nangini et al 16 ) between our predicted data and these other studies (Supplementary Fig.…”
Section: City-level Predictors Of Climate Emissionssupporting
confidence: 68%
“…These approaches can provide good estimates for major cities that disclose high-quality energy consumption data 16 . However, they can not be readily applied to a larger scale, where city-specific data are largely absent, especially for smaller cities 19 . Downscaling represents a solution to the scalability issue.…”
Section: Background and Summarymentioning
confidence: 99%
“…But the coverage, timeliness, and temporal resolution of these data are not always sufficient to support agile and informed decision making. For example, although several high-quality datasets are available for high-income countries, such as the Covenant of Mayors database ( https://www.globalcovenantofmayors.org/ 25 , 32 ) and OpenGHGmap ( https://openghgmap.net/ 19 ) for EU cities, and the Vulcan and Hestia datasets for U.S. cities ( https://vulcan.rc.nau.edu/ , https://hestia.rc.nau.edu/ 4 , 5 , 33 ), the tension between human development and decarbonization requires an increasing focus on rapidly expanding cities in low-income and emerging regions in South America, South and Southeast Asia, Africa and the Middle East where high-quality emission inventories are lacking 34 , 35 . Moreover, most existing city-level inventories have the issues of long time lag and low temporal resolution.…”
Section: Background and Summarymentioning
confidence: 99%